Comparison of Course Learning Outcomes Online vs. Face-to-Face: A Case Study (Journal on Excellence in College Teaching, 2024)
As online programs become more prevalent, institutions require assurance that learning quality in the online environment is comparable to that of a traditional, face-to-face classroom. This study focused on a single institution over a six-year period where learning is assessed using course learning outcomes (CLOs). Using a paired t test, the authors compared CLOs in only those courses taught using both face-to-face and online modalities within the same academic year. Results indicated no statistically significant difference in CLOs between the modalities. This analysis suggests that student learning was equivalent with respect to factual learning but does not address other aspects of learning, such as sense of community and interpersonal relationships.